ESSENTIAL OILS AS ANTIMICROBIAL AND ANTI-ADHESION AGENTS AGAINST BACTERIA SALMONELLA TYPHIMURIUM AND STAPHYLOCOCCUS AUREUS, AND YEASTS CANDIDA ALBICANS AND SACCHAROMYCES CEREVISIAE - Tomičić, Zorica; Tomičić, Ružica; Kocić-Tanackov, Sunčica; Raspor, Peter (Food and Feed Research, 2022)
A serious global problem with the increasing resistance of microorganisms to currently used antimicrobials, has opened up the promotional research in the identification of new, more effective drugs with a broad spectrum activity. Essential oils of plants, due to the large biological and structural diversity of their components, are known to have many potential benefits. The aim of this study was to evaluate the antimicrobial and anti-adhesion activity of fifteen essential oils and their compounds against two bacterial and two yeast species responsible for food spoilage and infectious diseases. Antimicrobial activity was determined by testing the minimum inhibitory concentration (MIC), the minimum bactericidal concentration (MBC) and the minimum fungicidal concentration (MBF) of essential oils and compounds. The essential oils of Cinnamomum zeylanicum and Eugenia caryophyllus showed the highest antimicrobial activity with MICs ranging from 0.078 to 1.25 mg/mL, and 0.039 to 1.25 mg/mL, respectively. On the other hand, essential oils of Aetheroleum eucalypti and Salvia officinalis had significantly weaker antimicrobial properties than the others. Further, MIC concentrations were used to assess the inhibition of adhesion of bacteria Salmonella Typhimurium ATCC 25923 and Staphylococcus aureus ATCC 14208, and yeast Candida albicans ATCC 10231 and Saccharomyces cerevisiae ATCC 9763 in a microtiter plate using the crystal violet staining method. Based on the percentage of adhesion inhibition, yeast S. cerevisiae ATCC 9763 showed a high level of antimicrobial resistance. E. caryophyllus essential oil had the strongest effect with inhibition up to 73 %. Consistent with the antimicrobial susceptibility results, the most active anti-adhesion compounds were carvacrol and thymol. Considering the role of biofilm in food spoilage and clinical diseases, inhibition of the initial phase of biofilm formation by natural antimicrobial agents may be an alternative to commonly used synthetic ones.